Understanding the issues of waqf at public university : preliminary findings - Norlaila Mazura Hj. Mohaiyadin; Aini Aman (Penerbit Universiti Kebangsaan Malaysia, 2021)
There are limited empirical studies on waqf management, especially in public university. Some studies highlighted the issues of accountability and transparency in managing the collection and distribution of waqf system that require further study. Using institutional logic, this study hopes to provide further understanding on the challenges faced by public university in managing waqf. This study uses qualitative research with a case study approach on a public university in Malaysia. Data collection covers interviews with stakeholders and document reviews. Preliminary findings show that there are some challenges in the accountability and transparency of waqf collection and distribution faced by public university. Theoretically, this study extends the understanding on the issues of accountability and transparency, particularly in waqf management. This study also recommends the best practices of waqf management for public university.